Mass spectrometry-based peptidome profiling of human serous ovarian cancer tissues. (February 2019) - Xu, Juan; Wang, Xusu; Xu, Pengfei; Liu, Siyu; Teng, Fang; Liu, Xiaoguang; Zhu, Qiaoying; Hua, Xiangdong; Gong, Zhen; Jia, Xuemei
Abstract: Background: Bioactive peptides existing in vivo have been considered as an important class of natural medicines for the treatment of diseases. Peptidome analysis of tissues and biofluids had provided important information about the differentially expressed bioactive peptides in vivo. Methods: Here, we analyzed the peptidome of serous ovarian cancer tissue samples and normal ovarian epithelial tissue samples by mass spectrometry and further investigated the possible bioactive peptides that were differentially expressed. Results: We identified 634 differentially expressed peptides, 508 of these peptides were highly abundant in serous ovarian cancer tissues, a result consistent with higher protease activity in ovarian cancer patients. The difference in preferred cleavage sites between the serous ovarian cancer tissues and normal ovarian epithelium indicated the characteristic peptidome of ovarian cancer and the nature of cancer-associated protease activity. Interestingly, KEGG pathway analysis of the peptide precursors indicated that the differentially regulated pathways in ovarian cancer are highly consistent with the pathways discovered in other cancers. Besides, we found that a proportion of the differentially expressed peptides are similar to the known immune-regulatory peptides and anti-bacterial peptides. Then we further investigated the function of the two down-regulated peptides in ovarian cancer cells and found that peptide P1DS significantly inhibited the invasion and migration of OVCAR3 and SKOV3 ovarian cancer cells. Conclusions: Our results are the first to identify the differentially expressed peptides between the serous ovarian cancer tissue and the normal ovarian epithelium. Our results indicate that bioactive peptides involved in tumorigenesis are existed in vivo.